Penyimpangan Maksim-Maksim Cara-Tujuan Sebagai Pembentuk Wacana Humor pada "Ini Talk Show" On Nett TV dan Implikasinya Sebagai Bahan Ajar Di SMA/SMK - Satomi, Arischa, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
ABSTRACT Purposes of the research are to: describe forms of means-ends maxims deviations as makers of humor discourses in "Ini Talk Show" On Nett TV, explain intention of the means-ends maxim deviation as a maker of humor discourse in "Ini Talk Show" On Nett TV, and know implications of the maxims deviations as teaching materials in high/vocational schools. The research is descriptive-qualitative one. Data was collected by using observation method and then, followed by technique of tapping. The technique was used to tap speeches from the 'Ini Talk Show" television program. Results of the research indicated that forms of means-ends maxims deviations as the makers of humor discourses in "Ini Talk Show" television program On Nett TV were caused because of the existence of: (1) acronym deviation, (2) deviation of ambiguity, (3) deviation of meaning extension, (4) straightforward deviation, (5) literal deviation, and (6) deviation of meaning changes. Intent of the means-ends maxims deviations as the makers of humor discourses in Ini Talk Show" On Nett TV was to make humor based on changes of meanings, changes of words forms and to bring out ideas or notions in speeches.